Impacts of selective logging on haemosporidian infection and physiological correlates in tropical birds. Issue 1 (January 2022) - Messina, Simone; Edwards, David Paul; Van Houtte, Natalie; Tomassi, Suzanne; Benedick, Suzan; Eens, Marcel; Costantini, David
Graphical abstract: Highlights: Selective logging of tropical forest was not associated with haemosporidian prevalence. Haemoproteus infections are significantly higher above forest understorey. Only Plasmodium- infected birds show altered nutritional and oxidative markers. Abstract: Tropical forest degradation affects host-parasite interactions, determining the probability of animals acquiring an infection. The activation of an immune response to fight off infections requires energy and other resources such as antioxidants which may be redirected from growth and reproduction. A key question is how selective logging—the most common form of tropical forest degradation—impacts the prevalence of avian haemosporidian infection and its correlated physiological responses (nutritional and oxidative status markers). We investigated the prevalence of Plasmodium, Haemoproteus, and Leucocytozoon parasites in 14 understorey bird species in lowland, logged and unlogged, old-growth forests of Borneo. Prevalences of infections were similar between selectively logged and unlogged forests. To explore nutritional and oxidative status effects of haemosporidian infections, we examined associations between infections and plasma proteins, plasma triglycerides, and multiple blood-based markers of oxidative status, testing for an impact of selective logging on those markers. Birds infected with Plasmodium showed higher levels of plasma proteins and non-enzymatic antioxidant capacity, and lower levels of plasma triglycerides and glutathione, compared with haemosporidian-free individuals. Conversely, birds infected with Haemoproteus showed no changes in nutritional or physiological markers compared with uninfected individuals. These results indicate higher metabolic and physiological costs of controlling Plasmodium infection, compared with Haemoproteus, possibly due to higher pathogenicity of Plasmodium. Selectively logged forests had no effect on the responses of birds to infection, suggesting that the environmental conditions of degraded forests do not appear to induce any appreciable physiological demands in parasitised birds.